PEMANFAATAN POHON AREN SEBAGAI SUMBER EKONOMI KELUARGA - Damayanti, Nidya Pravita; Sugianta, I Gede; Suwarni, Nani (Jurnal Penelitian Geografi (JPG), 2013)
The aim of this research was to find out the sugar palm tree utilization as an economic source for the families at Air Rupik village, Banding Agung subdistrict, South Oku district in the year of 2012, and it focused on the utilization of parts of the sugar palm tree which could be the economic source, the income from the sugar palm tree and the income donation from sugar palm tree for the families total income. In this research, the researcher used descriptive method. The population in the research were 30 people who constituted the research population. The primary data collecting techniques were done by Primary interviews and structured documentation, while the secondary data collecting technique was done by documentation. The data analysis of the research was table percentage. The results of this research indicated that: (1) sugar palm tree parts that maked use to pass processing process so that be family economic resources at water village rupik sugar palm leaf part is make use and cultivated to be palm leaf rib broom, flower part is maked use to taken nira pass process penyadapan in tuna (tandan) male flower good flower also female flower, fibre of palmtree part has been maked use for direct sold to fibre of palmtree collectors shaped fibre of palmtree copies that cleaned, fruit part is maked use to made kolang-kaling, stick part or sugar palm tree at water village rupik maked use only stick that old and unproductive again to made household tools likes knife handle, axe stalk, also upon which building shaped wood, sugar palm aereal root part is maked use to cultivated to be medicine in the form of liquid that called arrack. (2) The average income from the sugar palm tree utilization was Rp 995,000,- per month. (3) The contribution from the sugar palm tree utilization for the families total income were less than 50 % that is as big as 46%. Key Words : The sugar palm tree utilization, average income permonth, income donation